2017
DOI: 10.1097/mpa.0000000000000745
|View full text |Cite
|
Sign up to set email alerts
|

Role of Combined 68Ga-DOTATOC and 18F-FDG Positron Emission Tomography/Computed Tomography in the Diagnostic Workup of Pancreas Neuroendocrine Tumors

Abstract: The high sensitivity of Ga-PET/CT in NET detection is known. The high PPV of F-PET/CT in the identification of G2 forms suggests its potential role in PanNETs prognostication and risk stratification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(71 citation statements)
references
References 24 publications
4
66
0
1
Order By: Relevance
“…In all nine patients the disease progressed 25. Some teams are investigating dual-tracer imaging for preoperative prognostication and risk stratification in pancreatic tumors or pulmonary carcinoid 27,28. Lococo et al showed that a ratio of ≥1.19 between the SUVmax on SRI-PET and the SUVmax on FDG-PET can differentiate between a typical or atypical carcinoid 28.…”
Section: Are Results Of Sri-pet and Fdg-pet Complementary?mentioning
confidence: 99%
“…In all nine patients the disease progressed 25. Some teams are investigating dual-tracer imaging for preoperative prognostication and risk stratification in pancreatic tumors or pulmonary carcinoid 27,28. Lococo et al showed that a ratio of ≥1.19 between the SUVmax on SRI-PET and the SUVmax on FDG-PET can differentiate between a typical or atypical carcinoid 28.…”
Section: Are Results Of Sri-pet and Fdg-pet Complementary?mentioning
confidence: 99%
“…To our knowledge, this is the first prospective study evaluating the impact of combined 68 Ga-DOTANOC and 18 F-FDG-PET/CT in predicting the aggressive behavior of NF-PNET. There is some previous data of the dual-tracer imaging with series of different gastroenteropancreatic neuroendocrine tumors [18,24] and retrospective series of PNETs [17,25]. The main interest of this study was to evaluate if the malignant potential of NF-PNETs could be predicted with dual-tracer PET/CT imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Garin et al [24] investigated prospectively well-differentiated metastatic NETs and reported that 18 F-FDG-positivity correlated with decreased progression free survival and overall survival. Cingarlini et al [17] compared retrospectively G1 and G2 PNETs and concluded that 18 F-FDG-PET/CT was positive in a smaller proportion of G1 tumors (20%) compared with G2 tumors (76%). In our study 34% NF-PNET patients had a positive 18 F-FDG-PET/CT and the 18 F-FDG-PET/CT showed a PPV of 78% in the detection of potentially aggressive tumors (G2, G3, LN+ or M+ PNETs), and the NPV was 69%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, previous studies on small groups of patients with EP NENs suggest that 18F-FDG PET might be of value for detecting more aggressive tumors with high proliferative Ki67 index [15,16]. A role for 18F-FDG PET, alone or in combination with 68Ga PET, has also been proposed, with conflicting results, in some series of NENs with a more aggressive clinical course [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%